# Finding a length (x) inside a circle sector given another length (y) and the arc length (s) [closed]

I am stuck on a problem and can not seem to find a solution, maybe someone here can help me or at least tell me if it is possible to solve?

The problem is: Find the length $x$ given the length $y$ and the arc length $s$. The circle sector angle is unknown but less than 90 degrees.

## closed as off-topic by Travis Willse, Alex Mathers, Shailesh, colormegone, choco_addictedMay 19 '16 at 4:04

This question appears to be off-topic. The users who voted to close gave this specific reason:

• "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – Travis Willse, Alex Mathers, Shailesh, colormegone, choco_addicted
If this question can be reworded to fit the rules in the help center, please edit the question.

• The solution involves $\operatorname{sinc}^{-1}$ which has no simple closed form. – kennytm May 18 '16 at 17:02
• I suspected something like that, thank you! – Ville May 18 '16 at 17:06

Suppose the section angle is $\theta$ and radius is $r$, then we have

\begin{align} s &= r\theta, \tag1 \\ y &= r\sin\theta, \tag2 \\ x &= r - r\cos\theta. \tag3 \end{align}

Using (2)/(1) we find that \begin{gather} \frac{\sin\theta}\theta=\frac ys \iff \theta = \operatorname{sinc}^{-1}\frac ys. \\ r =\frac y{\sin\theta} = \frac y{\sin(\operatorname{sinc}^{-1}\frac ys)} \end{gather} Thus $$x = r(1-\cos\theta) = \frac{y\left(1-\cos\theta\right)}{\sin\theta} = y\tan\frac\theta2=y\tan\left(\frac12\operatorname{sinc}^{-1}\frac ys\right).$$

There is no simple inverse of the sinc function, so we cannot simplify further.

First let there be an arbitrary radius r.

By the arc length formula, $$r\theta=s$$

Now consider the pythagorean theorem.

$$r^2=y^2+(r-x)^2$$ $$0=y^2-2rx+x^2.$$ $$2rx=y^2+x^2$$ $$r=(y^2+x^2)/2x$$

Therefore $$s=\theta(y^2+x^2)/2x$$ $$2xs/(y^2+x^2)=\theta$$ Now $$sin(2xs/(y^2+x^2))/y=sin(\pi/2)/r$$ $$sin(2xs/(y^2+x^2))=2xy/(x^2+y^2)$$ But $$cos(2xs/(y^2+x^2))=(r-x)/r=1-2x^2/(x^2+y^2)$$ so, by the sin^2+cos^2=1 identity, $$1-4x^2/(x^2+y^2)+4x^4/(x^4+2x^2y^2+y^4)+4x^2y^2/(x^4+2x^2y^2+y^4)=1$$ Simplifying, this is actually just a true statement. The closest we can get to a solution is thus the previous finding: $$sin(2xs/(y^2+x^2))=2xy/(x^2+y^2)$$ This can be used to solve s in terms of x and y, but you need infinite series to solve for x in terms of y and s.